Pembuatan Biodiesel Dari Sawit Off-Grade Dengan Proses Dua Tahap - Rahmawati Rahmawati; Zuchra Helwani; Yelmida A (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Off-grade palm oil is a source of untapped vegetable oil. Off-grade palm oil can be used as an alternative raw material for biodiesel production despite having high content Free Fatty Acid (> 5%). Plant with a capacity of 30 tones of FFB yield 7-10% off-grade palm oil or 2-3 tons per hour. The catalyst used is potassium hydroxide because it has smaller ionization energy, making it faster to form a product when used as a catalyst. This research aims to produce biodiesel from low-quality raw materials and determine the effectiveness of the process by looking at the effect of process conditions such as reaction temperature, molar ratio and catalyst concentration on the yield of biodiesel. The biodiesel making process was carried out with two stages of the reaction, esterification and transesterification reactions due to high content of free fatty acid in the raw material. Data processing in this study was analyzed by response surface methodology (RSM) using Design Expert 8.0 program. Experiment runs were determined by central composite design (CCD), which consists of three variables, namely temperature, catalyst concentration and molar ratio of methanol to oil. The highest biodiesel yield was 88.56% (%wt) obtained under the conditions of reaction temperature 60 °C, the molar ratio of methanol to oil 8:1 and the concentration of 1% KOH base catalyst. The characteristics of biodiesel produced in the form of density, kinematic viscosity, acid number and flash point are in accordance with the standards of Indonesian biodiesel. Catalyst concentration have a significant influence on the yield of biodiesel.Keyword : off-grade palm oil, biodiesel, base catalyst, esterification and transesterification